PENERAPAN METODE PEMBELAJARAN COLABORATIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR SISWA KELAS IV UPTD SD NEGERI 124397 JL. STADION DALAM PEMBELAJARAN MATEMATIKA - Simanjuntak, Melvin; Jojor Parisma Simangunsong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the effectiveness of collaborative learning methods in improving the motivation to learn mathematics of grade 4 students. The type of research used in this study is a pre-experimental research type with a one group pre-test post-test design. This design uses two measurements of students on the material to be sampled. The results showed a significant increase in the learning motivation of students in the experimental group compared to the control group. This shows that collaborative learning methods are effective in improving the motivation to learn mathematics of grade 4 students.